2022
DOI: 10.1111/grs.12367
|View full text |Cite
|
Sign up to set email alerts
|

Selenite uptake by Medicago sativa L. roots

Abstract: This study aimed to examine selenite uptake in Medicago sativa L. Potted alfalfa plants were grown in sterilized quartz sand and exposed to 1 and 10 μM selenite for 21 days.Thirty-day-old seedlings and excised roots were used to determine the mechanism of selenite uptake in alfalfa. The following patterns of Selenium (Se) distribution in roots were as follows: lateral roots > taproots and subcellular fraction (I) > fraction (III) > fraction (II). With increasing pH, Se uptake in roots decreased markedly. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The inhibition of selenite uptake at low concentrations (≤4 μM; 316 μg l −1 ) by phosphate addition to the test water indicated that this anion was a key competitor. This hypothesis that selenite uptake likely occurs through a phosphate transporter is consistent with studies on selenite uptake in plants and yeast ( Lazard et al, 2010 ; Araie et al, 2011 ; Zhang et al, 2014 ; Vriens et al, 2016 ; Wang et al, 2019 ; Bai et al, 2022 ). The finding of selenite uptake in D. magna via a phosphate transporter is further supported by the effect of application of the phosphate transporter inhibitor PFA/foscarnet, wherein increased levels of this blocker reduced selenite uptake.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The inhibition of selenite uptake at low concentrations (≤4 μM; 316 μg l −1 ) by phosphate addition to the test water indicated that this anion was a key competitor. This hypothesis that selenite uptake likely occurs through a phosphate transporter is consistent with studies on selenite uptake in plants and yeast ( Lazard et al, 2010 ; Araie et al, 2011 ; Zhang et al, 2014 ; Vriens et al, 2016 ; Wang et al, 2019 ; Bai et al, 2022 ). The finding of selenite uptake in D. magna via a phosphate transporter is further supported by the effect of application of the phosphate transporter inhibitor PFA/foscarnet, wherein increased levels of this blocker reduced selenite uptake.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in human erythrocytes, selenite uptake is likely achieved by the bicarbonate/chloride anion exchanger (AE1 or Band 3 or SLC4A1; Kaur et al, 2020 ), while McDermott et al (2016) suggested selenite uptake was associated with ZIP8 (SLC39A8) and was transported into a variety of mammalian cells along with zinc and bicarbonate as part of an electroneutral transport process. In plants, considerable research links selenite uptake to phosphate transporters ( Zhang et al, 2014 ; Wang et al, 2019 ; Bai et al, 2022 ), and evidence also exists for phosphate transporter-mediated selenite uptake in yeast ( Lazard et al, 2010 ) and in phytoplankton ( Araie et al, 2011 ), although in both groups alternative pathways have also been suggested (monocarboxylate transporters in yeast; McDermott et al, 2010 ; sulphate and nitrate transporters in phytoplankton; Morlon et al, 2006 ). In the bacterium Escherichia coli , selenite uptake is proposed to be achieved by a sulphate transporter ( Lindblow-Kull et al, 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable crops are Horticulturae 2024, 10, 209 2 of 23 the main source of dietary Se intake for the human body, so planting Se-rich crops is of great significance for supplementing Se to the human body [9]. Se is mainly utilized by plants in the form of inorganic salts, such as selenite (SeIV) and selenate (SeVI), which are absorbed within the plant through sulfate transporters, and selenite enters the plant through active transport mediated by phosphate transporters [10,11]. Earlier studies in mustard showed that PHO1-H8 promoted the absorption of Na 2 SeO 3 by mustard roots, while SULTR 3;3 and SULTR 4;1 promoted the transport of Se from the roots to shoots and chloroplasts.…”
Section: Introductionmentioning
confidence: 99%